Tax Avoidance Perusahaan Perbankan - Ivan Andalenta; Kun Ismawati (Owner : Riset dan Jurnal Akuntansi, 2022)
There were many unconsistent research result about “what and how” tax avoidance’s influencers. This study aims to determine the factors that influence the tax avoidance of banking companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2018 period. The research population consisted of 26 Food and Beverage Companies listed on the IDX, with 9 companies that successfully sampled and meet the criteria. Cross section data is used in this research. The data analysis techniques used multiple regression analysis, simultaneous test, coefficient of determination test, and partial test. The results of the study state that profitability as measured by ROA has a significant effect on tax avoidance in the banking industry on the Indonesia Stock Exchange for the 2016-2018 period. Leverage as measured by DER has a significant effect on tax avoidance in the banking industry on the Indonesia Stock Exchange for the 2016-2018 period. Profitability (ROA) and leverage (DER) simultaneously have a significant effect on tax avoidance in the banking industry on the Indonesia Stock Exchange for the 2016-2018 period.